2022
DOI: 10.32604/cmc.2022.022553
|View full text |Cite
|
Sign up to set email alerts
|

Hypo-Driver: A Multiview Driver Fatigue and Distraction Level Detection System

Abstract: Traffic accidents are caused by driver fatigue or distraction in many cases. To prevent accidents, several low-cost hypovigilance (hypo-V) systems were developed in the past based on a multimodal-hybrid (physiological and behavioral) feature set. Similarly in this paper, real-time driver inattention and fatigue (Hypo-Driver) detection system is proposed through multi-view cameras and biosignal sensors to extract hybrid features. The considered features are derived from non-intrusive sensors that are related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…By comparing the facial expressions of a great number of normal people with those of psychopaths, a theoretical model for emotional decoding of human behaviour and facial expressions was developed [ 26 ]. Riquelme et al collected a large amount of facial expression data of drivers and extracted feature codes to develop a driver fatigue monitoring system, which detects the driver's mouth aspect ratio, blinking frequency, and head tilt angle to determine whether the driver is in fatigue and alerts control staff in time, so as to avoid traffic accidents [ 27 ]. In a study on classroom teaching, Schneider et al found that facial expressions are expressions of mental activity and that different facial expressions have a greater impact on learning efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By comparing the facial expressions of a great number of normal people with those of psychopaths, a theoretical model for emotional decoding of human behaviour and facial expressions was developed [ 26 ]. Riquelme et al collected a large amount of facial expression data of drivers and extracted feature codes to develop a driver fatigue monitoring system, which detects the driver's mouth aspect ratio, blinking frequency, and head tilt angle to determine whether the driver is in fatigue and alerts control staff in time, so as to avoid traffic accidents [ 27 ]. In a study on classroom teaching, Schneider et al found that facial expressions are expressions of mental activity and that different facial expressions have a greater impact on learning efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in medical applications (Fu et al, 2023; Jiang et al, 2020; Liu et al, 2019), psychologists determine a patient's condition by constantly observing changes in the patient's facial expressions to suggest a treatment plan. In the application of fatigue driving (Abbas et al, 2022; Xiao et al, 2022), if the in‐vehicle detection system detects signs of fatigue driving in the driver's facial expressions, it will emit an alarm to remind the driver. In sales applications (Ijjina et al, 2020), customers' facial expressions are essential data for computers to determine whether they need a human sales assistant.…”
Section: Introductionmentioning
confidence: 99%